Claimed eaudiobook - Young, Mila (Haven Realm, 2018)
Little Mermaid. Three spirited warriors. A realm in peril. As the princess in the underwater realm, Nyssa has many responsibilities, none of which included an arranged marriage to the cruel, possessive, and scheming army commander. Desperate to escape the union at all costs and save the kingdom from his merciless ways, Nyssa makes a dangerous pact with the sea witch. With the help of three mersoldiers who pledge their allegiance to her, Nyssa must track down a magical pearl to save her and her kingdom. But staying ahead of the commander is a deadly game. One that threatens to tear her from the mermen claiming her heart, leaving her to navigate new emotional currents while keeping her head above, or below, water. Mermaids, loyalty, passion and vengeance collide in this spellbinding romance that finds its "Happily Ever After." Contains mature themes.